INTERNET AS A DRIVER OF POLITICAL CHANGE: CYBER-PESSIMISTS AND CYBER-OPTIMISTS (Journal of the Spanish Institute for Strategic Studies, 2013)
There are two schools of thought about the impact of Internet on the processesof political change. On the one hand, individuals who believe thatthis technology has some features that promote the spread of democracyaround the world, and those who believe that this instrument consolidatesauthoritarianism and political repression. The purpose of thisarticle is a descriptive analysis of the main arguments used for both tojustify their positions. This work defends the argument that both viewsattribute a deterministic role to Internet which does not correspond toits neutral nature. In contrast, the effects of Internet on political changedepend on the context and the ability of actors who use it